Biomaterials from the sea: Future building blocks for biomedical applications - Mei-chen Wan; Wen Qin; Chen Lei; Qi-hong Li; Meng Meng; Ming Fang; Wen Song; Ji-hua Chen; Franklin Tay; Li-na Niu (Bioactive Materials, 2021)
Marine resources have tremendous potential for developing high-value biomaterials. The last decade has seen an increasing number of biomaterials that originate from marine organisms. This field is rapidly evolving. Marine biomaterials experience several periods of discovery and development ranging from coralline bone graft to polysaccharide-based biomaterials. The latter are represented by chitin and chitosan, marine-derived collagen, and composites of different organisms of marine origin. The diversity of marine natural products, their properties and applications are discussed thoroughly in the present review. These materials are easily available and possess excellent biocompatibility, biodegradability and potent bioactive characteristics. Important applications of marine biomaterials include medical applications, antimicrobial agents, drug delivery agents, anticoagulants, rehabilitation of diseases such as cardiovascular diseases, bone diseases and diabetes, as well as comestible, cosmetic and industrial applications.